Implementasi Chatbot Telegram untuk Meningkatkan Kualitas Layanan Jaringan Internet Pada Layanan ICONNET Menggunakan Penerapan Metode Action Research (AR) - Yuwan, Ridho Pangestu; R. Soelistijadi; Zuliarso, Eri (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This study focuses on implementing a Telegram chatbot in ICONNET, a leading internet service provider, to improve the quality of its network services. Employing the Action Research (AR) methodology, the research aims to enhance customer satisfaction and optimize operational efficiency through iterative cycles of planning, implementation, evaluation, and reflection. The literature review highlights the potential of chatbot technology in various service sectors, emphasizing its ability to reduce response time, improve customer service, and streamline operations. However, limited research has specifically explored the implementation of chatbots on the Telegram platform within the context of Internet network services. Through active stakeholder involvement, including service users and network operators, the study emphasizes the importance of personalization, accuracy, and promptness in chatbot responses to drive customer satisfaction. Thorough analysis and evaluation will assess the impact of the Telegram chatbot implementation on improving the quality of ICONNET internet network services. The findings will provide practical recommendations for other internet service providers seeking to adopt chatbot technology to enhance customer experience and operational efficiency. By contributing to the advancement of chatbot technology and the improvement of internet network services, this research expands our understanding of chatbot implementation within the domain of information technology services. The study sheds light on the benefits and challenges of implementing a Telegram chatbot and offers valuable insights for further research and industry practitioners